2016
DOI: 10.1016/j.rasd.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Looking behind the mask: Social coping strategies of girls on the autistic spectrum

Abstract: The socio-communication deficits of individuals on the autistic spectrum are well documented. However, this has largely been based on the male population and less is known about how females with autism manage social relationships across the developmental period.Ten adolescent female participants with a diagnosis of autism were interviewed and Interpretative Phenomenological Analysis used to explore their experiences of managing their social relationships. The results showed that participants were motivated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
282
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(298 citation statements)
references
References 23 publications
9
282
2
5
Order By: Relevance
“…However, closer examination reveals autistic girls may have significant difficulties maintaining friendships and dealing with conflict, and therefore are not functioning socially to the same extent as their typically developing peers [56]. As previously described, both intuitive and explicit camouflaging techniques mean that adolescent girls can mask their ASD characteristics from others around them, even in clinical settings [62]. Autistic girls and adolescents may therefore miss out on official diagnosis for years due to lack of awareness of their difficulties from others around them.…”
Section: Missing Women: Co-occurring Conditions and Environmental Fitmentioning
confidence: 96%
See 3 more Smart Citations
“…However, closer examination reveals autistic girls may have significant difficulties maintaining friendships and dealing with conflict, and therefore are not functioning socially to the same extent as their typically developing peers [56]. As previously described, both intuitive and explicit camouflaging techniques mean that adolescent girls can mask their ASD characteristics from others around them, even in clinical settings [62]. Autistic girls and adolescents may therefore miss out on official diagnosis for years due to lack of awareness of their difficulties from others around them.…”
Section: Missing Women: Co-occurring Conditions and Environmental Fitmentioning
confidence: 96%
“…Simultaneously, several self-reported anecdotes and a few newly emerging studies have identified camouflaging techniques used by autistic females to mask and distract from their ASD difficulties, and to present a more socially competent self than they actually feel [61,62]. These strategies, which are used both to cope with ASD difficulties and minimise others' awareness of them, may result in under-identification of females who are struggling with their ASD, as the outward portrayal to teachers or clinicians is of someone who is developing typically [59,63].…”
Section: Camouflaging By Femalesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the accuracy of autistic stereotypes has been brought into question, with evidence suggesting that the vast majority of autistic people are not savants (Conn and Bhugra, 2012;Draaisma, 2009;Freeman-Loftis, 2015), or emotionless (Tierney, Burns and Kilbey, 2016). With this in mind, Garner, Jones and Harwood (2015) conducted a study using the Childhood Autism Rating Scale (CARS, 2) (Schopler, Van Bourgondien, Wellman et al, 2010) to measure the accuracy of film portrayals of autistic people according to 15 behavioural categories (e.g., relating, listening and intellect).…”
Section: Introductionmentioning
confidence: 99%